Degrowth, energy descent, and 'low-tech' living: Potential pathways for increased resilience in times of crisis. (1st October 2018) - Alexander, Samuel; Yacoumis, Paul
Abstract: The use or misuse of advanced technology is a key factor driving global environmental degradation, but advanced technology is also widely assumed to be the solution to many environmental problems. In contrast to that dominant approach, this paper outlines a variety of what the authors call 'low-tech' options – such as solar shower bags, washing lines, alternative heating and cooling methods, and cycling – and raises questions about the extent to which these types of 'simple living' practices could help increase household resilience in conditions of economic disruption, instability, or crisis. The analysis is framed by an 'energy descent' scenario, in which an individual, household or community either chooses a reduced-energy way of life, motivated by climate change mitigation, or has such a way of life imposed upon them due to declining fossil fuel availability or economic disruption. The authors see such a future as plausible – and in some contexts has already arrived or has always been the case – hence the relevance of this analysis, which has both quantitative and qualitative dimensions. Furthermore, while the focus herein is on low-tech living at the household level, it is argued that prefiguring a 'simpler way' to live has deeper significance too, in that it could help create the cultural conditions needed for a politics and macroeconomics of degrowth to emerge, which the authors maintain is a necessary part of any decarbonisation project. Challenges facing low-tech options are also acknowledged, including the ever-present risk of rebound effects and other indirect impacts. Highlights: 'Low-tech' options which do not require fossil fuels or electricity to operate are examined. Examples include solar shower bags, washing lines, alternative heating methods, and cycling. These 'simple living' practices can reduce energy use, although the rebound effect is always a risk. Low-tech options could increase 'resilience' in times of energy scarcity or economic disruption. Low-tech options may represent a culture of degrowth from which a politics of degrowth could emerge.